Concursos públicos de língua portuguesa na Rede de Ensino do Estado de São Paulo: uma análise comparativa dos editais para o ingresso de professores (1992, 1998, 2003) - Santos, Idê Moraes dos (2013)
The purpose of this study is to analyze the Portuguese Language Teacher Profiles that were published to determine eligibility to take the Entrance Examinations to be considered for positions with the São Paulo State Schools. This study focuses on the published profile announcements for the Entrance Exams for the years 1992, 1998, and 2003. Further stated, this study looks only at a fraction of the public announcements which correspond to the Entrance Examinations for the subtests of General Education Knowledge and Specific Portuguese Language Knowledge during this time. There have been very few studies done on the topic of Entrance Examination Profiles in the São Paulo State System and those that have been done have been restricted to, in most cases, an analysis of the test itself and not the profile requirements to take the test. Consequently, the requirements published to take the entrance examinations do not encompass all of the considerations of best preparation and best practice to ensure high standards of teaching. Therefore, the candidates who take the test may be ill prepared to pursue a successful teaching career. Due to this discrepancy, the test itself and the public announcement that determines eligibility to test must be considered separately. The Portuguese Language Teacher Profile public announcements determining eligibility to take the examination during the period cited above are very problematic. Upon closer consideration, the public announcements at times advertised for the ideal candidate who would become a successful teacher yet at other times, the announcements reflected a standard that was insufficient to fulfill the basic duties of a teacher. This may be explained by the fact that the public announcements for eligibility to take the Entrance Exams are crafted by and often reflect the interests of the local governing bodies and serve to legitimize and publicize their own agendas. These agendas more often than not do not reflect best educational practices. Once these announcements are published, they may be construed as appropriate educational practice by the general public. A more grave consideration is that these faulty proclamations become the basis for legislation that negatively impacts educational policy for all schools in São Paulo State. With respect to the curricula content in the discipline of Portuguese during the time cited above, it was found that there were wildly divergent aspects in the published announcements. This was most blatantly seen on the list of literary classics from 1992